Optical studies of silicon quantum dots for improving solar cells efficiency / Adam Ikhwan Abdul Malik - Adam Ikhwan, Abdul Malik (2018)
Research in quantum dots (QD) in these recent years have been encouraging. Various QD research has shown its capability to utilise various quantum effect including photon conversion, ‘Hot Electron Carrier, the ‘Multiple-Exiton Generation’ and ‘Plasmonic light trapping’. These are new areas of research within the realm of quantum dots and photovoltaic energy conversion but as of writing this report, there has been no major breakthrough in the QD development themselves. One of the limiting factors in QD research is the optical studies for solar cell application. This research paper is the study of optical application of QD in sensitised thin film solar cells with an objective to improve cell efficiency through optical control. Optical properties is one of the important QD criteria to look for in solar application. General research done on QD and recent optical properties researches of QD are discussed. The method of calculation is the use of WIEN2K to derive an electronic band structure properties of the material before applying the result to an optical calculations. The results will be compared with a different empirical study that has compiled their own result of optical properties and bandgap properties. The paper concludes that there is a strong correlation between the electrical properties of a semiconductor and its optical properties but calculating the electrical properties from a known optical properties requires more work.